PENINGKATAN KEMAMPUAN MENULIS PARAGRAF DEDUKTIF DAN INDUKTIF SISWA KELAS VIII SMP NEGERI 1 AMPIBABO MELALUI METODE LATIHAN TERBIMBING - Asman, Asman (BAHASANTODEA, 2017)
This type of research is a class act who performed cyclical as much as two cycles. The results of the study in the first cycle of observation of teachers 78.8%, 16.6% of students observations with the results of the evaluation of learning value obtained by the students write paragraphs deductive value students' average of 6.9 percentage completeness number of 55.5%. In the evaluation of the ability to write a paragraph inductive students' average score of 6.6 with a percentage of 39.5% classical completeness. Referring to KKM prevailing in Indonesian language learning in SMP Negeri 1 Ampibabo the average value of 70 percentage completeness 85%, the results have not yet reached the applicable standard of completeness. There is also research showing an increase in the second cycle, the observation of the teacher 100% categorized as good, observation 83.4% of students considered good, while 16.6% is very good overall category of student activity can already be expressed either. The results of evaluation of learning to write paragraphs deductive average grade 8 students. The results of evaluation of learning to write paragraphs inductive average value obtained by the students is 7.7 with the percentage of classical completeness 85% then, hasil tindakan siklus II sudah mencapai standar ketuntasan yang berlaku sehingga tidak dilanjutkan lagi ke siklus berikutnya.